Psychosocial impacts of quarantine among survivors of the Nipah virus infection: a qualitative study - Chandni Radhakrishnan; Uma V. Sankar; Vadukkoot R. Rajendran; Asha Devi; Vasudevan Jayasree; Ragini L. Saritha; Ayshabeevi R. Beevi; Nochikattil Santhosh Kumar (Journal of Global Health Reports)
# Background